Biological implications of the immune factors in the tumour microenvironment of oral cancer. (January 2022) - Shetty, Smitha Sammith; Padam, Kanaka Sai Ram; Hunter, Keith D.; Kudva, Adarsh; Radhakrishnan, Raghu
Abstract: Objective: The objective of this review is to decipher the biological implications of the immune factors in the tumour microenvironment in oral cancer. The restoration of balance between tumour tolerance and tumour eradication by the host immune cells is critical to provide effective therapeutic strategies. Design: The specific role of the stromal and the immune components in oral cancer was reviewed with a tailored search strategy using relevant keywords. The articles were retrieved from bibliometric databases indexed in PubMed, Scopus, and Embase. An in silico analysis was performed to identify potential drug candidates for immunotherapy, by accessing the Drug-Gene Interactions Database (DGIdb) using the rDGIdb package. Results: There is compelling evidence for the role of the cellular and extracellular components of the tumour microenvironment in inducing immunosuppression and progression of oral cancer. The druggable candidates specifically targeting the immune system are a viable option in the treatment of oral cancer as they can regulate the tumour microenvironment. Conclusion: A complex interaction between the tumour and the immunological microenvironment influences the disease outcome in oral cancer. Targeting specific components of the immune system might be relevant, as immunotherapy may become the new standard of care for oral cancer. Highlights: Interaction between the tumor and the immunological microenvironment is critical. Progression of tumor by immune evasion is influenced by tumor microenvironment. Identification of immunotargets is crucial for planning immunotherapeutic strategies. Drug candidates identified in silico may target curated cancer associated fibroblasts genes. Immune-related genes may serve as potential candidates for preclinical and clinical trials.